A Theo-Pedagogical Study on Learning Christianity Based on the Israeli Shema for Contextual Education - Hasibuan, Serepina Yoshika; Marpaung, Agus Marulitua (Sekolah Tinggi Teologi Transformasi Indonesia, 2025)
Abstract:The learning of spirituality in Christian Religious Education (CRE) is often trapped in cognitive-informative patterns without regard to relational and contextual depth. This article responds to the need for a more integrative and applicable Christian learning practice by exploring the Shema of Israel (Deut. 6:4-9) as a conceptual basis. The formulation of the problem raised is: how can the principles of spirituality learning in Shema Israel be constructed as a contextualised CRE learning practice? The purpose of this research is to construct Biblical text-based spirituality learning using a hermeneutic method through a theo-pedagogical approach for contextual Christian education. This research uses a literature study method by putting the theoretical concept on the theory of faith growth from John H. Westerhoff III. The research found four dimensions of religious learning from the Shema of Israel, namely relational, repetitive, visual, and rhythmic. These four dimensions can be implemented in contextual CRE through intergenerational practices, sustainable pedagogy, visualisation of learning design and integration of faith in the context of life. This research recommends learning practices that build relationships, are continuously repeated, visualised and embedded in the rhythm of daily life as a living and meaningful expression of faith.